2019
DOI: 10.1002/cti2.1090
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing naive‐ from memory‐derived human B cells during acute responses

Abstract: Objectives A fundamental question in influenza research is whether antibody titre decline upon successive exposure to variant strains is consequent to recall of cross‐reactive memory B cells that competitively inhibit naive B‐cell responses. In connection, it is not clear whether naive and memory B cells remain phenotypically distinct acutely after activation such that they may be distinguished ex vivo. Methods Here, we first compared the capacity of anti‐Ig and Toll‐like‐receptor (TLR) 7/8 and TLR9 agonists (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
(99 reference statements)
1
13
0
Order By: Relevance
“…We thus further analyzed the distribution of memory B cells in PEDV-inoculated pigs by examining the level of antibodies produced by MNCs isolated from blood and each tissue following in vitro stimulation. We stimulated isolated MNCs with the TLR7/8 agonist R848, which induces polyclonal memory B-cell expansion and antibody production without a specific antigen [ 37 , 48 50 ]. Because B-cell responses can vary depending on the dose and virus proteins used for stimulation [ 32 , 51 ], we hypothesized that in vitro stimulation with R848 may provide a clearer picture of memory B-cell responses to PEDV than stimulation with recombinant proteins or partially purified viruses.…”
Section: Discussionmentioning
confidence: 99%
“…We thus further analyzed the distribution of memory B cells in PEDV-inoculated pigs by examining the level of antibodies produced by MNCs isolated from blood and each tissue following in vitro stimulation. We stimulated isolated MNCs with the TLR7/8 agonist R848, which induces polyclonal memory B-cell expansion and antibody production without a specific antigen [ 37 , 48 50 ]. Because B-cell responses can vary depending on the dose and virus proteins used for stimulation [ 32 , 51 ], we hypothesized that in vitro stimulation with R848 may provide a clearer picture of memory B-cell responses to PEDV than stimulation with recombinant proteins or partially purified viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that R848 induces the activation of CD4 + Th1 cells and CD8 + cytotoxic T lymphocytes ( 8 , 55 ), promotes the proliferation of B cells and inhibits their apoptosis ( 21 , 56 , 57 ). Recently, R848 was demonstrated to enhance human B cell differentiation induced by IL-21 and sCD40L ( 58 ). In mice, R848 augments the proliferation of the bone marrow CD11c + B lymphocyte population ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, B cells survive the ex vivo cultures in the presence of stimulation with synthetic ligands, such as TLR7/8 and TLR9 agonists, which help B cells to activate and differentiate into plasma cells in antigen non-specific manner (den Hartog et al, 2018;Jahnmatz et al, 2013). Also, R848 and CpG augment the non-specific proliferation of the B cells in presence of T cell derived factors, IL-21 and CD40L (Auladell et al, 2019;Franke et al, 2020). Besides, enhanced survival and proliferation of B cells was associated with the accumulated monocytes in the tumor microenvironment (Epron et al, 2012).…”
Section: Discussionmentioning
confidence: 99%